Pandangan Al-Qur’an Tentang Perempuan: Kritik Terhadap Tuduhan Kaum Feminisme - Dony Arung Triantoro (Cakrawala: Jurnal Studi Islam, 2018)
The pheniminists appear to respond to the oppression and backwardness of women to men. The allegations of western feminism against women's backwardness over men are due to religious teachings as contained in the QS. an-Nisa ': 1, 11, 12 and 34. This article aims to answer the allegations of phenimism by comparing opinions between classical and contemporary mufassirs. The methods used in this article are through literature studies. This article finds that the classical mufassir in understanding the revelation of the nafs in the QS. an-Nisa ': 1 as Adam, while contemporary mufassir understand it as one (same) type. Then the classical mufassir in understanding ar-rijalu qawwamuna 'ala an-nisa' in the QS. an-Nisa: 34 because of the intellectual, physical, and educational advantages of men. Whereas contemporary mufassirs understand men's leadership over women with men's duty to safeguard, protect and control and suffice women's needs as a consequence of that leadership. Then the classical mufassir in understanding men gains inheritance over women in QS. an-Nisa: 11-12 is due to his intellectual and responsibility towards women, while contemporary mufassirs interpret the verse by the cancellation of the law that was in the ignorance of women who did not inherit. Finally this article indicates that allegations of feminism are basically directed to the interpretation of classical mufassir in understanding the verses concerning the position of women